PENGARUH LINGKUNGAN, KOMPENSASI DAN KOMPETENSI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. INFOMEDIA NUSANTARA JAKARTA - Nazifah Husainah; Cecep Haryoto; Desi Satriani (Cross-border, 2023)
One of determining factors in the field of human resources is adapting to the work environment, providing compensation, increasing competence in creating new changes to create employee job satisfaction in order to achieve company goals according to the vision and mission. The purpose of this study was to determine the positive influence of work environment variables, compensation and competence on job satisfaction employees of PT. Infomedia Nusantara Jakarta. The research method used is quantitative research with an associative approach. Sampling in this study used a sample of 60 respondents. The data collection method used was a questionnaire, while the data analysis used in this study was carried out by testing the validity, reliability test, classical assumption test, multiple linear regression analysis, correlation coefficient test, coefficient determination test, and hypothesis testing. The results of the study show that the variables of work environment, compensation and competence have a significant effect of 80.5% on employee job satisfaction and the remaining 19.5% is explained by other factors not seen from this study and are positively related which means that the higher the work environment variable , compensation and competence, the higher it also affects employee job satisfaction at PT. Infomedia Nusantara Jakarta.